Level Of Anxiety In Patients Undergoing Elective Gastroscopy With General And Local Anesthesia - Audrey Yohan Agnes*; OK Yulizal; Yensuari Yensuari (Riwayat: Educational Journal of History and Humanities, 2023)
Gastrointestinal endoscopy involves the examination of the mucous membranes of the esophagus, stomach, and duodenum using an instrument equipped with a camera to provide visual images. This procedure has numerous clinical applications, including accurate diagnosis and effective guidance for upper gastrointestinal tract conditions. Insufficient patient knowledge about the impending procedure, potential procedural side effects, or anticipated examination outcomes can lead to heightened anxiety of the patient. This study aims to assess the level of anxiety in patients undergoing gastroscopy. An observational analytical study was conducted using a cross-sectional design, based on the Hamilton Anxiety Rating Scale (HARS) questionnaire. Moderate anxiety was found in 25 individuals (50%) among patients undergoing gastroscopy with local anesthesia. Meanwhile, among patients undergoing gastroscopy with general anesthesia, 15 individuals (30%) exhibited mild anxiety, and 5 individuals (10%) had moderate anxiety. There is a discernible difference in anxiety levels between patients undergoing elective gastroscopy with general anesthesia and those receiving local anesthesia.